Ghrelin expression of endometrium hyperplasia and endometrioid carcinoma - Dagli, Adile F.; Aydin, Suleyman; Kocdor, Hilal; Gurates, Bilgin; Sahin, Ibrahim; Catak, Zekiye; Ozercan, Ibrahim H. (Taylor & Francis Ltd, 2011)
Background. Endometrium carcinoma ranks fourth among female carcinomas. Therefore, early diagnosis of endometrium pre-malignant lesions is emphasised, and attempts are made to identify the risk factors. Since hyperplasias, particularly those with atypia, are held responsible for the development of the most common endometrium carcinomas, it is important to definitely distinguish between well-differentiated carcinomas and hyperplasia with atypia. In the present study, we aimed to explore whether ghrelin expression had a role in distinguishing between benign, pre-malignant and malignant lesions of endometrium. Methods. Tissue ghrelin expressions of a total of 60 cases, who were diagnosed in the Pathology Department Laboratory of FiA +/- rat University Medical School, and of whom 10 were in the proliferation phase, 10 had simple hyperplasia without atypia, 10 had simple hyperplasia with atypia, 10 had complex hyperplasia without atypia, 10 had complex hyperplasia with atypia and 10 had endometrioid carcinoma cases, were examined using immunohistochemical method. Additionally, tissue samples were homogenised to analyse tissue ghrelin levels in the supernatants according to RIA method. Samples from the parotid glands were used as positive control for ghrelin. Cells that exhibited cytoplasmic staining with ghrelin antibody were evaluated as positive. Results. Immunohistochemical examination showed that ghrelin expression increased markedly in the proliferation phase, relative to hyperplasias and carcinoma. These results were parallel to ghrelin levels in tissue supernatants. Immunohistochemical and RIA analysis results indicate that ghrelin expression either markedly decreases or is entirely depleted in endometrial carcinomas. Conclusions. Therefore, we think that ghrelin expression can be useful in differentiating not only endometrium carcinomas from benign lesions but also complex hyperplasias with atypia, which pose diagnostic difficulties.
Keywords: Ghrelin; proliferation phase; simple hyperplasia; complex hyperplasia; endometrioid carcinoma